Генетический анализ энтомофага вида Trichogramma pintoi Voeg. - Мельничук, М.Д.; Спиридонов, В.Г.; Ясинская, Н.П.; Облап, Р.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Investigations of the genetic structure of internal noncoding transcribed spacer 2 (ITS2) of ribosomal DNA of Trichogramma pintoi Voeg. are done. The performed PCR-analysis with the following nucleotide sequence determination of ITS2 region allowed us to reveal essential inter-specific distinctions. The obtained data can be used for the T. pіntoі species identification.